2010
DOI: 10.1084/jem.20091990
|View full text |Cite
|
Sign up to set email alerts
|

ADAM10 is essential for Notch2-dependent marginal zone B cell development and CD23 cleavage in vivo

Abstract: The proteolytic activity of a disintegrin and metalloproteinase 10 (ADAM10) regulates cell-fate decisions in Drosophila and mouse embryos. However, in utero lethality of ADAM10−/− mice has prevented examination of ADAM10 cleavage events in lymphocytes. To investigate their role in B cell development, we generated B cell–specific ADAM10 knockout mice. Intriguingly, deletion of ADAM10 prevented development of the entire marginal zone B cell (MZB) lineage. Additionally, cleavage of the low affinity IgE receptor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
158
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(163 citation statements)
references
References 56 publications
3
158
2
Order By: Relevance
“…It was long held that MZB cells emanate from progenitors with a CD23 + T2B phenotype that express CD1d and CD21 6,10,17,41 . Others have also proposed that FoB cells can develop into MZB cells, particularly in immunodeficient and lymphopenic hosts, a process that might be driven by homeostatic proliferation 24,41,42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was long held that MZB cells emanate from progenitors with a CD23 + T2B phenotype that express CD1d and CD21 6,10,17,41 . Others have also proposed that FoB cells can develop into MZB cells, particularly in immunodeficient and lymphopenic hosts, a process that might be driven by homeostatic proliferation 24,41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…5). ADAM10 is known to cleave substrates when expressed on the cell surface, and we have reported that ADAM10 can be detected by flow cytometry on lymphocytes 10 . We found that 5-6% of CD93 + transitional B cells of the spleen of wild-type mice expressed ADAM10 on their cell surface, yet this expression was almost completely absent in Taok3 -/-mice 9 (Fig.…”
mentioning
confidence: 96%
“…Previous studies have shown that ADAM10 and ADAM28 may be essential for Notch2‐dependent MZ B‐cell development 26, 27, 28. qRT‐PCR analysis showed that Transitional B cells expressed the high level of ADAM10, whereas MZP B cells expressed the high level of ADAM28 (Fig.…”
Section: Resultsmentioning
confidence: 77%
“…ADAM10 has been shown to be essential for the development of MZ B cells 28. A recent study demonstrated that T1 B cells expressing surface ADAM10 were committed to becoming MZB cells in vivo , whereas T1 B cells lacking expression of ADAM10 were not 26.…”
Section: Discussionmentioning
confidence: 99%
“…FO B cells can be further subdivided into FOI and FOII B cells, where the latter represent long-lived recirculating B cells that were suggested to serve as a reservoir to replenish MZ B cells [13]. Tg animal models have identified several determinants important for MZ B-cell development and maintenance, including Notch [14,15], NF-κB [9,16], and BCR signaling [17,18]. In order to unravel the role of Bcl-3 in B cells, we generated mice that overexpress Bcl-3 specifically in B cells.…”
mentioning
confidence: 99%